Effectiveness of Remote-Control Cars and Authentic Learning in Strengthening Creative Thinking and Problem-Solving Abilities - Ting-Ting Wu; Wei-Shan Liu (Educational Technology & Society, 2022)
Innovation in the design of curricula is widely discussed. Innovative curricula expose students to a diverse range of learning environments and prompt them to ask questions, stimulating their creativity and allowing them to develop a sense of initiative and to hone their problem-solving skills and ability to apply knowledge to practice. The introduction of new technology to the classroom has improved pedagogy and the information literacy of students. Because of these developments, this study expanded the integrative activity curriculum for second-grade elementary school students to an innovative curriculum involving a comprehensive set of activities related to remote-control cars and their use in the community. The students underwent a process of experiential learning in which they became familiar with the operation of remote-control cars. This study divided the students of two second-grade classes into an experimental group and a control group. The experimental group participated in innovative teaching activities as a part of authentic learning courses and were familiarized with the operations of remote-control cars in traffic in the community. The control group participated in innovative teaching activities as a part of the lesson plan for remote-control cars and were familiarized with the operation of the cars in traffic in the community. The creative thinking and problem-solving skills of the students in both groups significantly improved, and the students in the experimental group outperformed those in the control group. The students in both groups indicated that they were satisfied with the curriculum.